IMMERSED IN TRADITION: THE INTRICATE WEAVE OF THE SAPARAN TRADITION IN LODOSEWU VILLAGE AND ITS VIBRANT IMPACT ON COMMUNITY LIFE - Dilla, Chuna Kafia (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2023)
ABSTRACTThe Saparan Tradition for the Muslim community in Java, especially in Magelang is always eagerly awaited every year. Saparan can be referred to as Merti Desa, a term used by community to express gratitude to Allah who has given an abundance of blessings to the farmers for the harvest of the fields given. Saparan program invites relatives and friends from other areas. The Saparan Tradition in Lodosewu village has a different form of event from other areas, namely a tumpeng carnival and an arts carnival from the District Office to Lodosewu village. The carnival shows more meaning as the peopleâ€™s gratitude to Allah. The existence of Saparan in Lodosewu village has survived to this day because it has various functions for community. In this paper the author is interested in studying the Saparan Tradition and its function for the people of Lodosewu village. This research uses the theory of anthropology and symbolic interactionism to understand the meaning and the function of saparan tradition. This research is a field research using qualitative approach and the descriptive research is used to collect and analyze data. From the result of the analysis, it can be concluded that the result of the research is about the social cultural existence of the Lodosewu village people and the unique meaning from each process of Saparan.Keywords: Meaning, function, Saparan Tradition, Lodosewu village.Â ABSTRAKTradisi Saparan bagi masyarakat Muslim di Jawa, khususnya di Magelang selalu ditunggu-tunggu setiap tahunnya. Saparan ini bisa disebut sebagai Merti Desa, istilah yang dipakai oleh masyarakat untuk mengungkapkan rasa syukur kepada Allah. yang telah memberikan kelimpahan keberkahan kepada para petani atas panen ladang yang diberikan. Acara Saparan mengundang sanak saudara dan kerabat dari daerah lain. Tradisi Saparan di Dusun Lodosewu memiliki bentuk acara yang berbeda dari daerah lainnya, yaitu terdapat kirab tumpeng dan karnaval kesenian dari Kantor Kecamatan sampai Dusun Lodosewu. Kirab tersebut menunjukkan arti lebih sebagai rasa syukur masyarakat kepada Allah. Keberadaan Saparan di Dusun Lodosewu tetap bertahan hingga saat ini karena mempunyai fungsi yang beragam bagi masyarakat sehingga dalam tulisan ini penulis tertarik untuk mengkaji Tradisi Saparan serta fungsinya bagi masyarakat Dusun Lodosewu. Penelitian ini merupakan penelitian yang pengumpulan datanya dilakukan di lapangan, menggunakan metode deskriptif kualitatif. Dari hasil analisis dapat disimpulkan bahwa Tradisi Saparan dapat bertahan hingga saat ini karena masyarakat lebih menitikberatkan akar dari perayaan Saparan, yaitu syukuran bersama. Dalam hal tersebut makan bersama dan bersilaturahmi merupakan inti dari perayaan Saparan. Keberadaan Saparan memiliki makna di setiap pelaksanaannya.Kata kunci: Makna, Fungsi, Tradisi Saparan, Dusun Lodosewu.